Effects of spray nozzles and spray volume on spodoptera frugiperda management and narrow row corn performance - Gimenes, M. J. [UNESP]; Raetano, Carlos Gilberto [UNESP]; dal Pogetto, M. H F A [UNESP]; Prado, E. P. [UNESP]; Rezende, D. T. [UNESP]; Christovam, R. S. [UNESP] (Science Alert, 2012)
The high demand of pesticides in the production systems makes the application technology one of the main alternatives to optimize the products efficiency. In this context, the study aimed to evaluate the effects of spray nozzles and spray volumes on spraying deposits, armyworm control and crop corn performance in narrow row sowing system. The experiment was carried out at experimental area of Sao Paulo State University, Campus of Botucatu/SP, Brazil, during the 2009/2010 agricultural season, in randomized blocks with factorial scheme (2x2+1) and four replications. It was tested two flat fan spray nozzles (with and without air induction) combined with two spray volumes (100 and 200 L ha-1) plus a control treatment. There was no influence of spray nozzles (without air induction) in the spray deposits levels on plants. However, the flat fan nozzle with air induction was more effective on fall armyworm, with 100% of control against 47.84% from other at 15 days after spraying. The increase in the spray volume promoted high spray deposits (415.4 and 388.6 μL g-1 dry mass for flat fan nozzle with and without air induction, respectively at V10 growth stage) and consequently, the highest spray volume (200 L-1) was more efficient in the fall armyworm suppression, with 100% of control. All the technologies tested showed lower plant injury from fall armyworm. The insecticide sprayed with different technologies did not affect the parameters of plant height and leaf area index. The corn productivity was directly related with control efficiency of fall armyworm. © 2012 Academic Journals Inc.
Keywords: Application technology; Cropping systems; Fall armyworm; Phytosanitary management; Plant damage; Zea mays; Noctuidae; Spodoptera frugiperda